Actualization Of Islamic Religious Education In Character Formation - Fawaiz, Rohmatul (Jurnal Edusci, 2025)
Background. Allah SWT created humans as a caliph on earth. Allah SWT created humans with the main task of worship, as stated in the Qur'an. وما خلقت الجن والا نسى الا ليعبدون "I did not create jinn and human beings except for worship". Aims. Worship is the only human duty on earth. So, what is meant by worship? Worship means the devotion of a servant to his Lord in the land of his devotion is in community life by doing righteous deeds. Methods. Doing good to others solely because of Allah SWT. The nature of the commendable nature is like the nature of the preacher. Love, care, and sacrifice are the gates of peace and safety in the afterlife. Result. The teachings of Islam are so perfect, but the problem is, why in our country, which is a country with the highest followers of Islam, fraud, crime, fraud, selfishness, and tyranny still reign supreme in our beloved country? What is the problem? And is there a significant positive impact of an educational process? Has our da'wah method been effective? Have we understood the meaning of the teachings of Islam itself? Have we known ourselves? Who are we? How do we treat the Qur'an? Can we take the messages from the letters contained in the Qur'an? And what is our mindset or mindset in religion itself? Conclusion. These questions are a reference for the author in this article. Implementation. Actualization of Islamic religious education in character formation must be done.